Ab initio computational study of electronic structure part-1: reaction mechanism of peptide bond formation between amino acid alanine and glycine. (May 2019) - Dzikrullah, A; Cahyono, B; Laksitorini, M D; Siahaan, P
Abstract: The porosity of the peptide delivery pathway to the brain is hindered by the presence of tight junctions which are intercellular cadherin interactions, but this can be overcome by modulating the cadherin molecule using peptide derived synthesis, one of which is ADT-10 (Ac-QGA DTPPVGV-NH2 )' where there are amino acids glycine (G) and alanine (A). Formation reaction of the peptide is one of the most important chemical reactions, one way to probe the reaction of peptide synthesis is the computational method. The purpose of this research is to determine which mechanism of the reaction is most preferred to the synthesis of peptide bond formation between alanine and glycine from four pathways of the reaction mechanism, as well as glycine and glycine from two pathway of reaction mechanisms by ab initio computational approach. The calculations were carried out by theory and basis set HF/6-31g**. The results show the most preferred reaction of peptide synthesis of amino acid glycine and alanine is on the mechanism IV which result in Ac-GA-NH2 with activation energy 759.614 kJ⋅mol −1, while in glycine and glycine is on the mechanism II with an activation energy of 933.550 kJ⋅mol −1 .